Advanced Delivery System of Polyphenols for Effective Cancer Prevention and Therapy - Koung Hee Kim; Mi-Ran Ki; Ki Ha Min; Seung Pil Pack (MDPI AG, 2023)
Polyphenols from plants such as fruits and vegetables are phytochemicals with physiological and pharmacological activity as potential drugs to modulate oxidative stress and inflammation associated with cardiovascular disease, chronic disease, and cancer. However, due to the limited water solubility and bioavailability of many natural compounds, their pharmacological applications have been limited. Researchers have made progress in the development of nano- and micro-carriers that can address these issues and facilitate effective drug delivery. The currently developed drug delivery systems maximize the fundamental effects in various aspects such as absorption rate, stability, cellular absorption, and bioactivity of polyphenols. This review focuses on the antioxidant and anti-inflammatory effects of polyphenols enhanced by the introduction of drug delivery systems, and ultimately discusses the inhibition of cancer cell proliferation, growth, and angiogenesis.